2013
DOI: 10.1038/ncomms3405
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal nanoclusters and nanoparticles precede mineral formation in magmatic sulphide melts

Abstract: In low temperature aqueous solutions, it has long been recognized by in situ experiments that many minerals are preceded by crystalline nanometre-sized particles and non-crystalline nanophases. For magmatic systems, nanometre-sized precursors have not yet been demonstrated to exist, although the suggestion has been around for some time. Here we demonstrate by high temperature quench experiments that platinum and arsenic self-organize to nanoparticles, well before the melt has reached a Pt–As concentration at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…4e, j). The behavior of Te, Bi, As and Sb contrasts with that of Se which remains in solid solution in sulfide, by generally fractionating into immiscible telluride/bismuthide/arsenide and possibly antimonide melts on cooling and crystallization of a sulfide liquid (Helmy et al 2010(Helmy et al , 2013aHolwell and McDonald 2010;Prichard et al 2013). Furthermore, these melts sequester precious metals more effectively than sulfide melt (Helmy et al 2010).…”
Section: Precious and Semimetal Characteristics Of The Sulfidesmentioning
confidence: 94%
See 2 more Smart Citations
“…4e, j). The behavior of Te, Bi, As and Sb contrasts with that of Se which remains in solid solution in sulfide, by generally fractionating into immiscible telluride/bismuthide/arsenide and possibly antimonide melts on cooling and crystallization of a sulfide liquid (Helmy et al 2010(Helmy et al , 2013aHolwell and McDonald 2010;Prichard et al 2013). Furthermore, these melts sequester precious metals more effectively than sulfide melt (Helmy et al 2010).…”
Section: Precious and Semimetal Characteristics Of The Sulfidesmentioning
confidence: 94%
“…Furthermore, these melts sequester precious metals more effectively than sulfide melt (Helmy et al 2010). Although this appears to include a significant amount of Te in solid solution in sulfide, the high concentrations of Te at the base of the Cu zone may also represent the presence of some immiscible telluride melts associated with the sulfides in this zone (e.g., Helmy et al 2010Helmy et al , 2013a; though it is worth noting the dominant mineralogy of the PGE and Au remain as alloys.…”
Section: Precious and Semimetal Characteristics Of The Sulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…(phylum Apicomplexa, family Cryptosporidiidae) are coccidian protozoa affecting the gastrointestinal tract in several mammalian and amphibian species and only the lungs in birds (Helmy et al, 2013). Some of the members of this family possess also well expressed zoo-anthropogenic potential (Castro-Hermida et al, 2002).…”
mentioning
confidence: 99%
“…Recently, an increasing number of studies have reported the formation of nanocluster precursors and nanoparticles of PGEs under magmatic conditions (Bockrath et al 2004a;Ballhaus et al 2006;Finnigan et al 2008;Kogiso et al 2008;Helmy et al 2013;Wirth et al 2013;Junge et al 2015). In their pioneering studies on the PGE-chromite-sulphide system, Bockrath et al (2004a) and Ballhaus et al (2006) documented the formation of nanoparticles of metallic Ru and Ir below the liquidus temperature (1200-1360 °C) in low-pressure (0.5 GPa) experiments.…”
Section: Introductionmentioning
confidence: 95%